MANAGING AI TOOLS IN TRADITIONAL ART CURRICULUM - Kaushik, Sanchi; Singh, Dukhbhanjan; Acharya, Biswa Mohan; Bhosale, Varsha; Khurana, Divya S; Khurana, Shivam (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The swift onslaught of artificial intelligence in the creative domain has disturbed the long-held beliefs regarding the process of learning, rehearsing, and mastering visual arts. Conventional art education has long been based on embodied methods, including observation, repetition, sensual awareness, in which a sense of touching charcoal or feeling a brushstroke is a constituent of knowledge-making. The emergence of AI, starting with search engines of generated references and composition evaluators and palette proposed, opens up breathtaking opportunities and new contradictions. The study focuses on the way AI may be managed, organized and integrated into conventional studio based art education in an ethical way. It is a synthesis of the literature published on digital art pedagogy, a study of emerging technologies changing the concept of visual learning, and the development of a multi-layered management structure of art schools. The study suggests that AI should be placed in the role of a supportive mechanism that complements, but does not substitute perceptual, manual and reflective practices that comprise the core of the traditional art learning. An example is provided in the case studies, implementation guidelines and a proposed evaluation rubric to demonstrate how this integration can be operationalized without in any way making students less creative or less skilled. The paper ends with summarizing the future research opportunities, such as the long-term monitoring of AI-aided skill development, cultural aspects of AI-generated imagery, and regulatory frameworks governing how to keep the authenticity of the hybrid art-making conditions.